Dietary self-efficacy and social support interactions in junior athletes' acquisition of life skills - Shudo, Yuka; Yamaura, Kazuho; Yasuda, Jun; Sato, Ai; Ebi, Kumiko (Frontiers in Sports and Active Living, 2022)
Objective According to the stages of change, this study identified the association between dietary control self-efficacy and social support for healthy diets as factors influencing life skills acquisition in dietary habits among adolescents in Japan. Research design This cross-sectional study was conducted between April and May 2018 among eight high school baseball teams in Japan. Method Participants included 180 Japanese high school baseball players. Survey items evaluated life skills (dependent variables), self-efficacy's influence on dietary control, social support (explanatory variables), and stages of change. Hierarchical multiple regression analysis was used to reveal the associations. Results In the pre-action stage, although there was no significant association between the interaction of self-efficacy and social support on total life skills (β = 0.11, p = 0.158), a significant association was observed in the action/maintenance stage (β = 0.32, p < 0.05). The interaction between self-efficacy and social support showed a significant association with goal setting in the pre-action stage (β = 0.19, p < 0.05) and with communicating in the action/maintenance stage (β = 0.34, p < 0.05). Conclusion The acquisition of life skills amidst dietary situations can be facilitated by providing social support that considers self-efficacy in relation to dietary control, according to the stages of change.